A Meta-Ethnography on the Impact of Cancer for Lesbian and Queer Women and Their Partners. (April 2023) - Raque, Trisha L.; Ross, Kaitlin V.; Hangge, Anna R.; Gaines, Rebecca C.
Lesbian and queer women face unique experiences navigating cancer care, including challenges in accessing services that incorporate their relational supports. Given the importance of social support for survivorship, this study examines the impact of cancer on lesbian/queer women in romantic relationships. We conducted the seven stages of Noblit and Hare's meta-ethnography. PubMed/MEDLINE, PsycINFO, SocINDEX, and Social Sciences Abstract databases were searched. Two hundred and ninety citations were initially identified, 179 abstracts were reviewed, and 20 articles were coded. Themes were (a) intersectionality of lesbian/queer identity in the cancer context; (b) institutional and systemic supports and barriers; (c) navigation of disclosure; (d) characteristics of affirmative cancer care; (e) survivors' critical reliance on their partner(s); and (f) shifts in connection after cancer. Findings indicate the importance of accounting for intrapersonal, interpersonal, institutional, and socio-cultural–political factors for understanding the impact of cancer for lesbian and queer women and their romantic partners. Affirmative cancer care for sexual minorities fully validates and integrates partners in care, removes heteronormative assumptions in services provided, and offers LGB+ patient and partner support services.